A Struggling Phase Of A Tourism Village: A Case Study On Kemiri Tourism Village Jember - Gullit Tornado Taufan; Julien Arief Wicaksono; Mushthofa Kamal; Degita Danur Suharsono; Rizqi Febrian Pramudita (International Journal of Entrepreneurship and Tourism, 2023)
Since its opening on March 2021, Kemiri Tourism Village was, still, facing a number of problematic issues. The decreasing number of visitors was an alarming sign for the destination. Investigating the current condition of the tourism village was essential to get a comprehensive picture of what really happened. Based on that purpose, this case study was conducted by utilizing the concept of 4 As tourism components covering attraction, accessibility, amenities, and ancillary. The data was collected through interview with Kelompok Sadar Wisata (Pokdarwis), tourism awareness group, of Kemiri, observation to the destination, and content analysis on visitors’ reviews and other accessible sources regarding the tourism village. The results of the data analysis showed that the tourism village faced a number of issues based on the 4 As tourism components. Regarding the attraction, the tourism village needed to discover its unique attractiveness to make the destination distinctive from other tourism villages. In addition, when dealing with amenities, Kemiri Tourism Village should make a big effort to rebuild the destination due to the fact that there were a number of facilities that did not exist any longer when compared to its initial condition. Widening and strengthening partnerships were also essential to achieve better networking that would be beneficial to improve promotions.